Implementasi Demokratisasi Sudan - Kurniawan, Aucky Adi; Zahidi, Muhammad Syaprin (Indonesia Center for Middle East Studies, 2022)
The Sudanese people's demands led to the fall of Omar Bashir's administration, which had ruled the country for 30 years. Various ethnic conflicts, worsening economic conditions, and the South Sudan referendum were all elements that contributed to the Sudanese people's discontent with Omar Bashir's administration. The role and participation of practically all Sudanese people in mass actions with diverse demands that resulted in the regime's fall were the catalyst for democratization in Sudan, eventually forcing Omar Bashir to step down in 2019. This research used a qualitative approach to explore the situation of democracy in Sudan, as well as the role of the Sudanese people as a whole, in the midst of decades of internal conflict. The theory of democracy and the concept of civil society were used to analyze this situation. The involvement of the Sudanese people in bringing about improvements in the implementation of democracy and the people's ambitions to make Sudan a better and just country was found to be highly essential in this study.